WORKING CAPITAL MANAGEMENT AND FINANCIAL PERFORMANCE OF LISTED MANUFACTURING FIRMS IN KENYA (Cuea Journal of Business and Economics, 2024)
This study investigated the effect of working capital management on financial performance of listed manufacturing companies in Kenya. The specific objectives were to determine the effect of accounts receivable, cash, inventory and accounts payable management on the financial performance. The theories of Operating Cycle, just –in n-time (JIT), Cash Management, Inventory theory of Cash Management, and Cash Conversion Cycle were utilised for the study. The study used a descriptive longitudinal design. The target population was 9 listed manufacturing firms in Kenya. A census sampling method was used over the period 2014-2023. Secondary data was collected from the financial reports of the companies. Inferential and Descriptive statistics were applied to analyse the data using panel regression analysis with the help of EViews software. Accounts receivables and inventory management had significant negative effects on financial performance while cash and accounts payables management had insignificant effects on the financial performance. The study concluded that at 5% significance level, accounts receivable and inventory management had statistically significant negative effects on financial performance while cash and accounts payables management had no effect on financial performance. The study recommended that manufacturing firms should reduce the levels of accounts receivable and inventories to improve financial performance.